Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.jafc.2c06191
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Glycomic Characterization of Fiber from AOAC Methods Defines the Carbohydrate Structures

Abstract: Dietary fiber has long been known to be an essential component of a healthy diet, and recent investigations into the gut microbiome-health paradigm have identified fiber as a prime determinant in this interaction. Further, fiber is now known to impact the gut microbiome in a structure-specific manner, conferring differential bioactivities to these specific structures. However, current analytical methods for food carbohydrate analysis do not capture this important structural information. To address this need, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Glucose, fructose, and sucrose are the most abundant free mono-and disaccharides in raw corn according to Garret Couture et al (2021) [24], which is confirmed by the data of our study.…”
Section: Discussion Of Research Resultssupporting
confidence: 92%
“…Glucose, fructose, and sucrose are the most abundant free mono-and disaccharides in raw corn according to Garret Couture et al (2021) [24], which is confirmed by the data of our study.…”
Section: Discussion Of Research Resultssupporting
confidence: 92%
“…We envision our approach as a sensitive, highly customizable tool accessible to the food science community. The methodology is also readily incorporated into the more comprehensive multiglycomics workflow we have previously developed . Such a tool can ultimately provide insight into the structure of food and its relationship to human health by facilitating a high throughput that would be practically not achievable using existing standard analytical methods.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are still many studies focusing on the simultaneous separation of different types of monosaccharides. A different devitization method coupled with LC-MS/MS [45][46][47], and GC-MS [48][49][50] was developed for the accurate analysis of monosaccharides. Furthermore, NMR was also developed for the identification of pentosan polysulfate monosaccharide composition [51].…”
Section: Evaluation Of Monosaccharide Composition Determination Methodsmentioning
confidence: 99%